The Dual Epidemic Experience: Psychosocial Impact of COVID-19 on Ebola Survivors among Australian-Based West African Migrants - (:unkn) unknown (My University, 2024)
Introduction: Improvements in transportation has increased the risk of rapid infection transmission within communities and globally during outbreaks. Examples are the Ebola virus disease (EVD) epidemic in West Africa in 2014-2016 and the global COVID-19 pandemic in 2020-2022, that devastated and impacted the lives especially in low- income communities and hard to reach regional areas in high income countries such Australia. The Objective: of this study is an initial exploration of the psychosocial impact of the COVID-19 pandemic on West African migrants now living in Victoria Australia who experienced the EVD while residing in West Africa. Methodology: This was a narrative description of proposed cross-sectional mixed methods study. Qualitative component was designed to be individual interviews, while the quantitative would utilize SurveyMonkey©. The study population was focused on West African migrants, over the age of 18 years, living in Victoria, who resided in Ebola affected regions of West Africa during 2014-2016. Statistical analyses are proposed to involve mixed methods. Data collection methods: include an online survey which constituted closed ended quantitative component and qualitative text based open ended questions. Additional semi structured interviews will be conducted. Summaries from the Survey monkey will be further analysed utilising word cloud. Data from interviews will be transcribed with the aid of a computer and Yin’s five stages of qualitative data analysis will also be utilised on both data analysis before triangulation of findings from text-based questions and interviews. Expected findings: This study will provide a broad perspective of the impact of COVID-19, amongst West African migrants in Victoria who lived the 2014-2016 Ebola epidemic, an experience that can be valuable to migrants in similar situations globally. The expected findings will highlight how prior exposure to stressful situations and disasters such as what oc
Keywords: African Research